Paradigma pendidikan Islam : membangun masyarakat madani Indonesia - Sanaky, Hujair AH., 1954- (Yogyakarta : MSI, Universitas Islam Indonesia : Safiria Insania Press, 2003)
Concepts of Islamic education for the establishment of civil society in Indonesia
Originally presented as the author's thesis (S-2--Universitas Islam Indonesia, Yogyakarta, 2003) under title: Pembaruan pendidikan Islam menuju masyarakat madani Indonesia
Daftar pustaka : p. 305-329 and index
Keywords: Civil society -- Indonesia; Democracy -- Indonesia